PENURUNAN KADAR KATEKIN DAN KAFEIN TEH BOTOL SELAMA DALAM PROSES PRODUKSI - Bernadeta Soedarini (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2005)
Tea is the most popular beverage after drinking water throughout the world. In the recent year, tea has attracted significant attention caused by its reported health benefits, particularly the antioxidant, anticarcinogenic. and antiarteriosclerotic agent. It is generally believed that Flavonoids are mainly responsible for these actions. Flavonoids in tea are catechins and their derivates, such as epigallocatechin gallate (EGCG), epigallocatechin (EGC), epicatechine gallate (ECG)and epicatechin (EC). Catechins are colorless, water-soluble compounds, which will interact with caffeine, impart bitterness and astringency to tea confusion. Tea consumption has undergone a number of changes in many years. Since 1970, consumption of bottled tea has increased. A considerable factor in this change is the general trend toward convenience foods and packaging. The aim of this study was to evaluate the changing or caiechins and their derivates content, also caffeine, during processing of' bottled £ea production with HPLC method. The result of Excel analysis, show that tea leaves contain ECGC for the most compound (306.41 ppm), followed by ECG (41.67 ppm), EGC+C (40.02 ppm) and EC (21.99 pm) also caffeine ( 177.87 ppm). Based on Analysis of Variances (ANOVA). mother liquid tea has the most catechins and caffeine content. All compounds have significant decreased at the process of mixing. The decreased of catechins and caffeine content during bottling tea process were caused by dilution, oxidation and epimerization. After 3 days incubated, bottled tea relatively has no significant decreased, in EGCG (45.28 ppm), EGC + C ( 16.67 ppm), EGC ( I 0.11 ppm), EC (9.93 ppm) and caffeine ( 114.82 ppm).